2015
DOI: 10.1186/s12885-015-1201-5
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor and chemokine receptors 4 and 7 form a signaling axis to regulate CXCL12-dependent cellular motility

Abstract: BackgroundIdentifying cellular signaling pathways that become corrupted in the presence of androgens that increase the metastatic potential of organ-confined tumor cells is critical to devising strategies capable of attenuating the metastatic progression of hormone-naïve, organ-confined tumors. In localized prostate cancers, gene fusions that place ETS-family transcription factors under the control of androgens drive gene expression programs that increase the invasiveness of organ-confined tumor cells. C-X-C c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…However, the interaction of androgen with the CXCL12/CXCR4/CXCR7 system in the breast had not been studied until now. Androgen has been implicated in the regulation of breast cancer cell proliferation [55] and data from prostate cancer show that androgen modulates CXCR4 and stimulate cellular migration [23, 26], a result we extend to breast cancer in this investigation. In addition, castrated male rats have lower CXCL12 levels compared to control rats and after induced myocardial infarction, they display reduced ability to recruit CD34+ bone marrow cells to ischemic areas of the myocardium [25].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the interaction of androgen with the CXCL12/CXCR4/CXCR7 system in the breast had not been studied until now. Androgen has been implicated in the regulation of breast cancer cell proliferation [55] and data from prostate cancer show that androgen modulates CXCR4 and stimulate cellular migration [23, 26], a result we extend to breast cancer in this investigation. In addition, castrated male rats have lower CXCL12 levels compared to control rats and after induced myocardial infarction, they display reduced ability to recruit CD34+ bone marrow cells to ischemic areas of the myocardium [25].…”
Section: Discussionmentioning
confidence: 85%
“…The relation of estrogen and ERs with CXCL12 and CXCR4 in breast cancer cell proliferation and metastatic potential has been examined in depth during the last decade [17-22]. However, only a few reports have investigated the possible interaction between androgen/AR and CXCL12 and its receptors, mostly describing pro-migratory effects in prostate cancer [23-26]. …”
Section: Introductionmentioning
confidence: 99%
“…Taken together, our PLA results suggest that first, under control conditions (no E 2 , no LPS), GPR30 and ERa36 display a small amount of physical interaction, and none of these molecules interacts with p65. Furthermore, the investigators reported an "unexpected" CXCR7 localization in the nuclear compartment that modulates AR-mediated transcription [39]. Third, in the presence of LPS, both ERa36 and GPR30/ GPER1 strongly interact with NF-kB.…”
Section: Discussionmentioning
confidence: 96%
“…1B, lower). Nuclear localization of a G-coupled receptor has also recently been reported for CXCR7, interacting with another nuclear receptor superfamily member (AR) [39]. 1B.…”
Section: Hpms Express Only Era36 and Gpr30/gper1 Ersmentioning
confidence: 86%
“…Welsh et al detected that CXCL11 was highly expressed in PCa samples . CXCL11 regulated androgen‐regulated genes (ARGs) in LNCAP prostate‐tumor cells . In addition, CXCL11 could result in vascular smooth muscle cells proliferation and inhibited endometrial cancer growth with different CXCR3 isoforms .…”
Section: Discussionmentioning
confidence: 99%